A Miniaturized Multi‐Frequency Wide‐Band Leaky Wave Button Antenna for ISM/5G Communications and WBAN Applications. Issue 3 (13th March 2023) - Saeidi, Tale; Karamzadeh, Saeid
Abstract: A low‐profile multi‐frequency leaky wave button antenna for body‐centric communications is presented. A leaky wave antenna loaded with U‐slots (a combination of U‐slots and slits) and tapered slot structures to improve the radiation efficiency, broadside radiation pattern, and widen the steering range is designed. Furthermore, it comprises a whole ground to meet the Specific Absorption Rate standard requirements based on the known standards. The antenna's performances are examined for on and off‐body conditions. For demonstration, a prototype is implemented, and the measurement is performed on the chest. The antenna operates at multi bands of 1.7–3.3 GHz (Industrial, Scientific, and Medical and 5G communication) and 4.15–10 GHz (sub‐6 GHz and X‐band communications). The peak gains of 6.9 and 8.2 dBi were obtained for on and off‐ body conditions, respectively. Furthermore, the antenna offers maximum radiation efficiencies of 89.3% and 99.3% for on‐body and free‐space conditions. The specific absorption rate (SAR) values obtained for body‐centric communications meet the regulation requirements (e.g., on body tissue at 3.2 GHz, it is 0.78 (1 g) and 0.44 (10 g) W/kg). With an overall miniaturized size, the proposed button antenna could be integrated with clothes. In addition, a multi‐wide bandwidth, circularly polarized radiation, a small size, high efficiency and gain, and low SAR values prove that the proposed antenna can be a potential candidate for wireless body area network and simultaneous wireless information and power transfer applications. Key Points: Wearable and detachable miniaturized button antenna for fifth generation (5G) communications Wearable leaky wave antenna for beam scanning and power transfer applications High‐gain Wearable, and detachable low‐profile antennas for continuous wireless data transfer